Parents’ Perception Regarding Their Infants’ Pain Experience in the NICU - Fatima, Syeda Mah; Ashraf, Asma; Kauser, Syeda Tasneem; Perveen, Kausar (Biological and Clinical Sciences Research Journal, 2025)
Neonates admitted to the Neonatal Intensive Care Unit (NICU) often undergo multiple painful procedures, yet their inability to verbally communicate can lead to underestimation and inadequate management of pain. Parental involvement in pain assessment and management is crucial for improving neonatal outcomes; however, limited knowledge and confidence among parents may hinder their effective participation. Objective: To assess parents’ perceptions regarding their infants’ pain experiences in the NICU of a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 200 parents of infants admitted to the NICU using non-probability convenience sampling. Data were collected through a structured questionnaire that comprised demographic details and six perception items, rated on a Likert scale. Perception scores were categorized as positive (≥50%) or negative (<50%). Data were analyzed using SPSS version 21, with descriptive statistics applied to summarize the responses. Results: Most parents (71.5%) demonstrated a negative perception regarding their infant’s pain experiences. A majority (68.5%) strongly disagreed that they could identify when their baby was in pain, and 78.0% disagreed that they could reduce their baby’s pain. Confidence in performing kangaroo care was low, with only 31.0% agreeing they felt capable. Some parents expressed confidence in calming their infant, as 40.5% agreed they could soothe them to sleep during pain. However, fewer parents recognized the effectiveness of holding (38.0% agreed) or pacifiers (33.0% agreed) in stopping infant crying. Conclusion: The findings highlight significant gaps in parental confidence and awareness regarding infant pain recognition and management in the NICU. Targeted educational interventions are necessary to improve parental self-efficacy, foster active participation in pain management, and enhance neonatal care outcomes, particularly in resource-limited settings like Pakistan.